Particle Image Velocimetry (PIV) Investigation of Blade and Purge Flow Impacts on Inter-Stage Flow Field in a Research Turbine - Zhenyang Zhang; Hongwei Ma (Energies, 2019)
Flow field in the inter-stage is of great importance to jet engine turbine performance and efficiency. Investigation of flow fields is limited by the complex geometrical structure. Traditional measurement techniques, such as hot wire, pressure probe and laser Doppler velocimetry (LDV) can hardly obtain a planar information of the flow field simultaneously. To overcome this difficulty, an instantaneous planar velocimetry technique, the particle image velocimetry (PIV) technique is widely employed. However, there is no publication that studied the detailed flow field by PIV in a turbine inter-stage with the consideration of the influence of rotor blade and purge flow. This paper presents a quasi-three dimensional perspective of flow field between inlet guide vane (IGV) and rotor blade in a research turbine inter-stage by using a 2D PIV system. Coherent structures in the flow field are extracted by the proper orthogonal decomposition (POD) method. Time-averaged results show the ellipsoid structures caused by secondary flow in the inter-stage. Rotor blade influence to axial and radial flow is evaluated by time-averaged data and the first order POD mode. Egress of purge flow (9.4% of main annulus flow rate) leads to a domain with 60% axial velocity loss near hub and a growth over three times in radial velocity. POD analysis of purge flow shows detailed flow migration in the whole measurement plane.